The video game theory reader 2 [ - Perron, Bernard; Wolf, Mark J. P. (New York : Routledge, 2009)
Addresses contemporary issues such as convergence and MMORPGs. This title features an appendix of nearly 40 ideas and concepts from a variety of theories and disciplines that have been usefully and
Description based on print version record
Includes bibliographical references (p [389]-400) and index
Keywords: Video games